FRI0586 Interleukin (IL)-1 inhibition with anakinra and canakinumab in behÇet's disease related uveitis: a multicenter retrospective observational study. (15th June 2017) - Fabiani, C; Vitale, A; Emmi, G; Lopalco, G; Vannozzi, L; Guerriero, S; Gentileschi, S; Bacherini, D; Franceschini, R; Frediani, B; Galeazzi, M; Iannone, F; et al.
Abstract : Objectives: To evaluate the role of interleukin (IL)-1 inhibitors anakinra (ANA) and canakinumab (CAN) in the treatment of Behçet disease (BD)-related uveitis Methods: multicenter retrospective observational study including 19 consecutive BD patients (31 affected eyes) receiving treatment with anti-IL-1 agents. Data were analyzed at baseline, at 3 and 12 months. Primary end-point: reduction of ocular inflammatory flares (OIF). Secondary end-points: improvement of Best Corrected Visual Acuity (BCVA); reduction of macular thickness defined by optical coherence tomography (OCT) and of vasculitis identified with fluorescein angiography (FA); evaluation of statistically significant differences between patients treated with IL-1 inhibitors as monotherapy, subjects also administered with disease modifying anti-rheumatic drugs (DMARDs) and/or corticosteroids as well as between patients administered with IL-1 inhibitors as first line biologic treatment and those previously treated with TNF-α inhibitors Results: at 12 months OIF significantly decreased from 200/100 patients/year to 48.87/100 patients/year (p<0.0001). The frequency of retinal vasculitis identified by FA significantly decreased between baseline, 3-month and 12-month follow-up visits ( p <0.0001 and p =0.001, respectively). OIF rate was significantly higher in patients co-administered with DMARDs (81.8/100 patients/year) than in patients undergoing IL-1 inhibitors as monotherapy (0.0/100 patients/year) ( p =0.03). No differences were identified on the basis of corticosteroid use and between patients administered with IL-1 inhibitors as first-line biologic approach or second-line. Steroid dosage was significantly decreased at 12-month visit compared to baseline ( p =0.02). Conclusions: treatment with IL-1 inhibitors is effective in the management of BD-related uveitis and provides a long-term control of ocular inflammation in refractory and long-lasting cases. Disclosure of Interest: None declared